THE PEDAGOGICAL COMPONENT OF THE HEALTH PSYCHOLOGIST COMPETENCE - Krumina, Aira Aija; Mihailovs, Ivans Jānis (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
Pedagogical competence is an important integral component of health psychologist competence. The development of this component is implemented during two study courses in the Riga Stradiņš University, providing possibility for master programme „Health psychology” students to elaborate and pilot informal educational programs, trying to select and structure health psychology materials in accordance with the principles and requirements of pedagogy. The article analyze and evaluate the development of some transversal competencies and future skills of health psychologist’ during the practice, as well as to work out the recommendations for optimal practice organization in a professional environment. The article, based on students’ survey and results of the students’ developed informal educational programs analysis, show the process and the issues, which are important for educational programs elaboration and pedagogical competence development.